Analysis Water Quality in Reservoir of PDAM Tirta Bhagasasi Bekasi City Branch - Hendriani, Ardina; Rahmayanti, Henita; Sumargo, Bagus (International Journal of Science and Society, 2024)
Water is needed to support various living systems. Almost all of human life needs require water, both for household needs, agriculture, industry and other economic activities. It’s need for clean water increases along with the reduction in clean water available in the area, which if not managed properly, it can be scarcity. This type of research is quantitative descriptive. This research was conducted at the reservoir of Water Treatment Plant of PDAM Tirta Bhagasasi, Bekasi City Branch. Sampling was carried out for five days on January 29-February 2 in 2024. The parameters tested in this study are temperature, pH, turbidity, odor and taste. Testing was carried out at the PDAM Tirta Bhagasasi Laboratory. It aim of this research is to analyze the water quality in the reservoir of Water Treatment Plant in PDAM Tirta Bhagasasi Bekasi City and then the results are compared with the clean and drinking water quality standards in accordance with Minister of Health Regulation Number 32 of 2017. The results of the research show that the water quality of the Water Treatment Plant in PDAM Tirta Bhagasasi Bekasi City in terms of temperature, pH, turbidity, odor and taste parameters have fulfilled the standard of clean water by the government. Based on the results of this research, it is hoped that PDAM will continue to carry out regular inspections and cleaning of each Water Treatment Plant building, because this can affect water quality, where water quality is one of the most important factors in maintaining customer satisfaction with PDAM Tirta Bhagasasi Bekasi City Branch.